Variasi Rasio Amonium dan Nitrat terhadap Perkembangan Embrio Somatik Bawang Putih (Allium sativum) secara In Vitro - Singgih Tri Wardana (Jurnal Penelitian Sains, 2016)
This research was aimed to conduct different NH4 + : NO3 -ratios on the development of somatic embryos of garlic (Allium sativum) by in vitro technique. This research used complete random design with four levels of NH4 + : NO3 -ratios, i.e. 1:2, 1:3, 1:4, and 1:5.The cell suspension culture used MS medium with 0,25 mg l-1 BAP. The results showed that the different NH4 + : NO3 -ratios resulted significant effect on the development of somatic  embryos ( globular, scutelar, and coleoptiler stages).1:3 ratio of NH4 + : NO3 -was optimum to improve the development of somatic embryos.